Pengaruh Pengungkapan Akuntansi Lingkungan dan Mekanisme Good Corporate Governance Terhadap Kinerja Keuangan (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Erwin Febriansyah; Rakhel Fahreza (The Indonesia Capital Market Institute, 2020)
Purpose - The purpose of this study is to find out the importance of environmental accounting disclosures, the GCG mechanism proxied by the board of commissioners, the Board of Directors and the Audit committee on the financial performance of companies listed on the Indonesia Stock Exchange. Methods - This study uses a quantitative approach. the population in this study were companies listed on the Indonesia Stock Exchange during the period 2016-2018 and the samples used in this study were 22 companies listed on the Indonesia Stock Exchange. Data Analysis Techniques using Descriptive Statistics, Test classic assumptions, Analysis of Multiple Regression Equations, Hypothesis Testing and Determination Coefficient Testing (R-Squares). Finding - the findings in this study are the disclosure of environmental accounting has a positive influence and GCG Mechanism which is proxied by the board of commissioners and the audit committee has a negative effect and the board of directors has no influence on financial performance. still a small number of samples and objects in determination